Karya isthal pr bhawnatmak bhudhimatta: ek professional guide - Singh, Dalip; Rathore, Sachin (tr.) (New Delhi Sage, 2015)
The book catalogues the results of research in this area, and provides a conceptual understanding of emotional intelligence as the ability to manage moods, to motivate and lead people and also to empathize with them.
Keywords: IAS as an author (Batch 1982); Emotional intelligence; Psychology, Industrial